PA6 black non-heat-absorption composite material applied to automobile seat and preparation method of PA6 black non-heat-absorption composite material

By using components such as PA6 resin, ultra-high molecular weight polyethylene, SiO2 aerogel and SiO2 aerogel-glass fiber in car seat materials, the shortcomings of existing materials in terms of non-heat absorption are solved and excellent performance is achieved. The non-heat absorption and thermal conductivity make it suitable for parts such as car seats.

CN119350842APending Publication Date: 2025-01-24GUANGDONG GERUI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411705660.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing car seat materials have shortcomings in non-heat absorption, which is difficult to meet the high non-heat absorption requirements when people are in direct contact.

Method used

Adopt components such as PA6 resin, ultra-high molecular measuring polyethylene, SIO2 air gel, and SIO2 gas gel-glass fiber, etc., through co-mixed and modified treatment, prepare car seat composite materials with excellent non-thermal absorption and good thermal guidance. Essence

Benefits of technology

On the basis of ensuring the mechanical properties, the non-heat absorption and thermal conductivity of the composite material are significantly improved, which improves the riding experience and can be widely used in components such as car seats.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure YFZGEVRDEUUTC0A9AYFABOVQEF2ZCV1OQT4E4GAC
    Figure YFZGEVRDEUUTC0A9AYFABOVQEF2ZCV1OQT4E4GAC
Patent Text Reader

Abstract

The invention discloses a PA6 black non-heat-absorption composite material applied to an automobile seat and a preparation method. The PA6 black non-heat-absorption composite material is prepared from the following components: 80 to 100 parts of PA6 resin, 30 to 40 parts of ultrahigh molecular weight polyethylene, 15 to 20 parts of SiO2 aerogel, 10 to 15 parts of SiO2 aerogel-glass fiber, 10 to 20 parts of MBS, 2 to 4 parts of carbon black, 3 to 5 parts of ethylene-acrylate-maleic anhydride copolymer, 0.5 to 1 part of antioxidant 1010 and 1 to 2 parts of melamine polyphosphate. The prepared composite material has excellent mechanical properties, excellent heat resistance and heat insulation performance, and the flame retardant property reaches V-0 level; 15-20 parts of iO2 aerogel and SiO2 aerogel-glass fiber are used as additives, so that the composite material is endowed with excellent non-heat-absorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer composite materials, and in particular to a PA6 black non-absorbent composite material used for automobile seats and a preparation method thereof. Background Art

[0002] Polyamide (PA) is an engineering plastic with excellent properties such as high strength, heat resistance, wear resistance, and self-lubrication. It is widely used in many fields such as textiles, engineering, and automobiles. It is one of the indispensable materials in modern industry. In the manufacture of complete vehicles, the use of PA composite materials can significantly reduce the weight of car seats; it has good mechanical properties such as tensile strength and stiffness. Through reasonable design and material selection, the mechanical properties of composite seat beams can be significantly better than metal structures. While ensuring performance, the use of PA composite materials can control costs and will not significantly increase manufacturing costs, which helps to achieve cost-effectiveness. As a thermoplastic material, PA is easy to recycle, which is beneficial to the environmental protection and sustainable development of automotive parts; in addition, PA composite materials show good chemical stability and high temperature resistance. As a material for car seats, PA composite materials are a good choice.

[0003] CN114031932A discloses a modified plastic granule for automobile seat processing, which comprises the following components by weight: 60-80 parts of polyamide resin, 18-25 parts of polycarbonate, 6-12 parts of reinforcing agent, 2-5 parts of compatibilizer, 0.5-1 part of antioxidant and 0.1-0.5 part of heat stabilizer. The preparation method comprises the following steps: step 1, weighing polyamide resin, aromatic polycarbonate, compatibilizer and reinforcing agent in order by weight, mixing them into a mixing mixer, and stirring them evenly; step 2, weighing reinforcing agent, antioxidant and heat stabilizer in order by weight, adding them into the mixing mixer, and mixing them evenly; step 3, transferring them into a twin-screw extruder, extruding and granulating, and obtaining the product. The present invention improves the problem that the existing plastic granules for automobile processing have poor strength and are easy to break due to unreasonable composition and ratio, and the modified plastic granules prepared by the present invention also have the function of purifying VOC.

[0004] CN107936540A discloses an antistatic colorant seat material and a preparation method thereof, belonging to the technical field of seat material preparation. The antistatic colorant seat material comprises the following raw materials: PA, glass fiber, silicate whisker, coupling agent, conductive carbon black, antioxidant, silicone powder, dispersant, nano titanium carbide, nano tungsten carbide, tungsten silicide, tungsten powder, and the material is prepared through the steps of mixing, extrusion, drawing, pelletizing, drying, etc. The process of the present invention can significantly improve the tensile strength and cantilever beam notch impact strength of the material, and solve the problem of easy deformation of the seat.

[0005] CN109749438A discloses a low-smoke halogen-free flame-retardant nylon composite material and its application, comprising components: 40-70 parts of PA resin; 5-30 parts of phosphorus-based flame retardant; 1-20 parts of magnesium hydroxide. The present invention unexpectedly found through research that adding a certain proportion of magnesium hydroxide to the halogen-free flame-retardant nylon composite material can significantly reduce the smoke density of the material, improve the oxygen index of the material, and obtain an excellent low-smoke density and high-oxygen index modified product, which can be applied to aircraft seats, car seats, household appliances or other fields with high requirements for smoke density.

[0006] Existing research focuses on improving the mechanical properties of seat materials, and indeed has obtained automotive seat composite materials with better performance. However, there is less research on heat resistance. In order to provide a better car experience, especially for car seats that are in direct contact with people, the requirements for heat resistance are getting higher and higher. Therefore, the heat resistance of seat materials is also a research demand and direction for composite materials. Summary of the invention

[0007] Based on the needs and deficiencies of the prior art, the present invention provides a PA6 black non-absorptive composite material for automobile seats and a preparation method thereof. Under the premise of ensuring the mechanical properties of the composite material, the prepared composite material has excellent non-absorptive properties and good thermal conductivity, which provides better advantages for the riding experience and can be widely used in automobile seats and other components.

[0008] In order to solve the technical problem of this application and achieve the above-mentioned purpose, the technical solution provided by the present invention is as follows: A PA6 black non-absorbent composite material for automobile seats, comprising the following components in parts by weight: PA6 resin 80-100 parts, Ultra-high molecular weight polyethylene 30-40 parts, SiO 2 Aerogel 15-20 parts, SiO 2 Aerogel-glass fiber 10-15 parts, MBS 10~20 pieces, 2-4 parts of carbon black, 3-5 parts of ethylene-acrylate-maleic anhydride copolymer, Antioxidant 1010 0.5-1 part, 1 to 2 parts of melamine polyphosphate.

[0009] Furthermore, the composite material is composed of the following components in parts by weight: PA6 resin 80-100 parts, Ultra-high molecular weight polyethylene 30-40 parts, SiO 2 Aerogel 15-20 parts, SiO 2 Aerogel-glass fiber 10-15 parts, MBS 10~20 pieces, 2-4 parts of carbon black, 3-5 parts of ethylene-acrylate-maleic anhydride copolymer, Antioxidant 1010 0.5-1 part, 1 to 2 parts of melamine polyphosphate.

[0010] Furthermore, the composite material is composed of the following components in parts by weight: 85-95 parts of PA6 resin, Ultra-high molecular weight polyethylene 33-36 parts, SiO 2 Aerogel 17-18 parts, SiO 2 Aerogel-glass fiber 12-13 parts, MBS 14-16 pieces, Carbon black 2.5-3.5 parts, 4-5 parts of ethylene-acrylate-maleic anhydride copolymer, Antioxidant 1010 0.7-0.8 parts, 1.2 to 1.5 parts of melamine polyphosphate.

[0011] Furthermore, the molecular weight of the PA6 resin is 60,000-800,000 Da.

[0012] Furthermore, the molecular weight of the ultra-high molecular weight polyethylene is 5,000,000 to 6,000,000 Da.

[0013] Furthermore, the SiO 2 The preparation method of aerogel-glass fiber is as follows: (1) placing glass fiber in 0.5-1wt.% HF+1.5-2wt.% NH 4 F aqueous solution for 20-30s, rinse with deionized water, and dry; prepare a solution of γ-aminopropyltriethoxysilane, anhydrous ethanol, and deionized water in a mass ratio of (0.03-0.05): 1:0.2, raise the temperature to 70-80°C, and place the glass fiber, SiO 2 The aerogel is immersed in the above solution for 60 to 90 seconds, and ultrasonic stirring is used during the immersion process; (3) the solution of step (2) is filtered and heat-treated at 100 to 120° C. for 10 to 20 minutes to obtain SiO 2 Aerogel-glass fiber, spare.

[0014] Furthermore, the glass fiber has a length of 50 to 80 mm and an average fiber diameter of 5 to 10 μm.

[0015] The present invention uses PA6 resin as the main component, and selects ultra-high molecular weight polyethylene to be blended with PA6 resin to form an alloy material through experiments, which can significantly improve the mechanical properties of the composite material.

[0016] SiO 2 Aerogel is an excellent thermal insulation material with a nanoporous structure and a porosity of more than 90%. This structure greatly limits the heat conduction of gas molecules in the pores, thereby effectively reducing the thermal conductivity of the material. However, its application in polymer composites will lead to a decrease in thermal insulation performance due to compatibility and dispersibility, and will also lead to a significant decrease in the mechanical properties of the composite material. Based on this, the present invention starts from SiO 2 Starting from the modification of aerogel, to solve the problem of SiO 2 The performance of the aerogel is reduced by adding the rough glass fiber as the carrier. 2 Chemical and / or physical bonding between aerogels makes SiO 2 Aerogel adsorbed on the rough glass fiber surface.

[0017] MBS is a methyl methacrylate-butadiene-styrene terpolymer having a core-shell structure and can be used as a toughening agent and an impact modifier. More specifically, the shell layer of MBS is compatible with polyamide and UHMWPE matrices, which helps to improve the interfacial adhesion of the composite material, thereby enhancing the overall performance of the material. Based on this, the present invention preferably uses MBS.

[0018] A method for preparing a PA6 black non-absorbent composite material for automobile seats, comprising the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) PA6 resin, SiO 2 Aerogel and carbon black are poured into a stirring device and stirred evenly to form material group A; (3) Ultra-high molecular weight polyethylene, SiO 2 Aerogel-glass fiber, MBS, ethylene-acrylate-maleic anhydride copolymer, antioxidant 1010, and melamine polyphosphate are poured into a stirring device and stirred evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

[0019] Furthermore, the set temperature of the twin-screw extruder is: section one: 210-220°C, section two: 220-230°C, section three: 225-235°C, section four: 230-240°C, section five: 235-245°C, section six: 220-230°C, section seven: 215-225°C, section eight: 215-225°C, section nine: 220-230°C, and die head: 225-235°C.

[0020] Furthermore, the rotation speed of the twin-screw extruder is 300-400 rpm.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) With respect to automobile seat materials, the present invention provides a polymer composite material formed by blending polyamide 6 (PA6) and ultra-high molecular weight polyethylene (UHMWPE). The composite material has good mechanical properties, including high tensile strength, impact resistance and good wear resistance, so that the polyamide seat material is not only durable, but also able to withstand wear and impact in daily use.

[0022] (2) Creative use of SiO 2 Aerogel-glass fiber as an additive gives the composite material excellent non-absorbent properties.

[0023] (3) The composite material prepared by the present invention can not only be used as a car seat material, but also can be used in many fields. DETAILED DESCRIPTION

[0024] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0025] Main ingredients: PA6 resin is a product of Dongguan Chaolin Plastic Co., Ltd., with the brand name PF007. Ultra-high molecular weight polyethylene is a product of Ticona, USA, with the brand name GUR4150. MBS is a product of LG, brand EM500. The carbon black is high-pigment carbon black from Anyang Daimo New Materials Co., Ltd.

[0026] SiO 2 Aerogel is a product of Cabot Corporation of the United States, brand name IC3100, The glass fiber is a product of Taishan Glass Fiber Co., Ltd., brand T635B, SiO 2 Aerogel-glass fiber is a homemade product.

[0027] SiO 2Preparation of aerogel-glass fiber: (1) Place glass fiber in 0.7wt.%HF+1.8wt.%NH 4 F aqueous solution for 25s, washed with deionized water and dried; γ-aminopropyltriethoxysilane, anhydrous ethanol and deionized water were prepared into a solution according to a mass ratio of 0.04:1:0.2, the temperature was raised to 80°C, and the glass fiber and SiO 2 The aerogel was immersed in the above solution for 8 seconds, and ultrasonic stirring was used during the immersion process; (3) the solution of step (2) was filtered and heat-treated at 110°C for 15 minutes to obtain SiO 2 Aerogel-glass fiber, spare.

[0028] A PA6 black non-absorbent composite material for automobile seats, comprising the following components in parts by weight: 80 parts of PA6 resin, Ultra high molecular weight polyethylene 30 parts, SiO 2 Aerogel 15 parts, SiO 2 Aerogel-glass fiber 10 parts, MBS 10 copies, 2 parts of carbon black, 3 parts of ethylene-acrylate-maleic anhydride copolymer, 0.5 parts of antioxidant 1010, 1 part of melamine polyphosphate.

[0029] The method for preparing the above thermal composite material comprises the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) PA6 resin, SiO 2 Aerogel and carbon black are poured into a stirring device and stirred evenly to form material group A; (3) Ultra-high molecular weight polyethylene, SiO 2 Pour the aerogel-glass fiber, MBS, ethylene-acrylate-maleic anhydride copolymer, antioxidant 1010, and melamine polyphosphate into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

[0030] Among them, the set temperatures of the twin-screw extruder are: section one: 210°C, section two: 220°C, section three: 225°C, section four: 230°C, section five: 235°C, section six: 220°C, section seven: 215°C, section eight: 215°C, section nine: 220°C, and die head: 225°C.

[0031] Wherein, the rotation speed of the twin-screw extruder is 300 rpm.

[0032] A PA6 black non-absorbent composite material for automobile seats, comprising the following components in parts by weight: PA6 resin 100 parts, Ultra-high molecular weight polyethylene 40 parts, SiO 2 Aerogel 20 parts, SiO 2 Aerogel-glass fiber 15 parts, MBS 20 copies, 4 parts of carbon black, 5 parts of ethylene-acrylate-maleic anhydride copolymer, 1 part of antioxidant 1010, 2 parts of melamine polyphosphate.

[0033] A method for preparing a PA6 black non-absorbent composite material for automobile seats, comprising the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) PA6 resin, SiO 2 Aerogel and carbon black are poured into a stirring device and stirred evenly to form material group A; (3) Ultra-high molecular weight polyethylene, SiO 2 Aerogel-glass fiber, MBS, ethylene-acrylate-maleic anhydride copolymer, antioxidant 1010, and melamine polyphosphate are poured into a stirring device and stirred evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

[0034] Furthermore, the set temperature of the twin-screw extruder is: section one: 220°C, section two: 230°C, section three: 235°C, section four: 240°C, section five: 245°C, section six: 230°C, section seven: 225°C, section eight: 225°C, section nine: 230°C, and head: 235°C, wherein the rotation speed of the twin-screw extruder is 400rmp.

[0035] A PA6 black non-absorbent composite material for automobile seats, comprising the following components in parts by weight: 90 parts of PA6 resin, Ultra high molecular weight polyethylene 25 parts, SiO 2 Aerogel 18 parts, SiO 2 Aerogel-glass fiber 12 parts, MBS 15 copies, 3 parts of carbon black, 4 parts of ethylene-acrylate-maleic anhydride copolymer, 0.7 parts of antioxidant 1010, 1.5 parts of melamine polyphosphate.

[0036] A method for preparing a PA6 black non-absorbent composite material for automobile seats, comprising the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) PA6 resin, SiO 2 Aerogel and carbon black are poured into a stirring device and stirred evenly to form material group A; (3) Ultra-high molecular weight polyethylene, SiO 2 Aerogel-glass fiber, MBS, ethylene-acrylate-maleic anhydride copolymer, antioxidant 1010, and melamine polyphosphate are poured into a stirring device and stirred evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

[0037] Furthermore, the set temperatures of the twin-screw extruder are: section one: 215°C, section two: 225°C, section three: 230°C, section four: 235°C, section five: 240°C, section six: 225°C, section seven: 220°C, section eight: 220°C, section nine: 225°C, and die head: 230°C.

[0038] Wherein, the rotation speed of the twin-screw extruder is 350 rpm.

[0039] Comparative Example 1 Comparative Example 1 is consistent with Example 3, except that no ultra-high molecular weight polyethylene is added in Comparative Example 1.

[0040] Comparative Example 2 Comparative Example 2 is consistent with Example 3, except that Comparative Example 1 does not add SiO 2 Aerogel.

[0041] Comparative Example 3 Comparative Example 3 is consistent with Example 3, except that Comparative Example 1 does not add SiO 2 Aerogel-glass fibers.

[0042] The performance tests were carried out on the composite materials prepared above. The composite materials were first made into standard test specimens according to various national standard test specimens, wherein: the cantilever beam notched impact strength was measured according to the national standard GB / T1843, the tensile strength was measured according to the national standard GB / T1040, and the flexural strength was measured according to the national standard GB / T9341.

[0043] The thermal insulation property was characterized by measuring the thermal conductivity through a thermal conductivity meter; and after the composite material was irradiated with a UV lamp (40W) for 3h (irradiation distance 50mm), the temperature rise value (△T) was measured.

[0044] The blackness is characterized by measuring the L value according to GB / T7921-2008.

[0045] The specific test results are recorded in Table 1.

[0046] Table 1 The above test data show that the composite material prepared by the present invention has good mechanical properties, and its cantilever beam notched impact strength can reach 7.2 kJ·m -2 , the tensile strength can reach 75.1MPa, and the flexural strength can reach 91MPa, which can meet the basic application requirements of automobile seat materials; from the mechanical data of Comparative Example 1, it can be seen that without adding ultra-molecular weight polyethylene, the mechanical properties decrease significantly, which shows that ultra-molecular weight polyethylene can play a synergistic role with PA6 to improve its mechanical properties.

[0047] The composite material prepared by the present invention has excellent thermal insulation performance, and the thermal conductivity of the composite material is as low as 80mW / (m·K). The thermal conductivity of Comparative Examples 2-3 is significantly higher than that of Example 3; and the temperature rise value data is also higher than that of Example 3, which shows that SiO 2 Aerogel, SiO 2 The joint use of aerogel and glass fiber can better improve the thermal insulation performance of composite materials.

[0048] The composite material prepared by the invention has high gloss blackness, excellent flame retardancy and mechanical properties; it can be used not only as a car seat material, but also in many fields.

[0049] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A PA6 black non-absorbent composite material used for car seats, characterized in that: According to parts by weight, it includes the following components: PA6 resin 80-100 parts, Ultra-high molecular weight polyethylene 30-40 parts, 15-20 parts of SiO2 aerogel, SiO2 aerogel-glass fiber 10-15 parts, MBS 10~20 pieces, 2-4 parts of carbon black, 3-5 parts of ethylene-acrylate-maleic anhydride copolymer, Antioxidant 1010 0.5-1 part, 1 to 2 parts of melamine polyphosphate.

2. The composite material according to claim 1, characterized in that According to parts by weight, it is composed of the following components: PA6 resin 80-100 parts, Ultra-high molecular weight polyethylene 30-40 parts, 15-20 parts of SiO2 aerogel, SiO2 aerogel-glass fiber 10-15 parts, MBS 10~20 pieces, 2-4 parts of carbon black, 3-5 parts of ethylene-acrylate-maleic anhydride copolymer, Antioxidant 1010 0.5-1 part, 1 to 2 parts of melamine polyphosphate.

3. The composite material according to claim 1, characterized in that According to parts by weight, it is composed of the following components: 85-95 parts of PA6 resin, Ultra-high molecular weight polyethylene 33-36 parts, 17-18 parts of SiO2 aerogel, SiO2 aerogel-glass fiber 12-13 parts, MBS 14-16 pieces, Carbon black 2.5-3.5 parts, 4-5 parts of ethylene-acrylate-maleic anhydride copolymer, Antioxidant 1010 0.7-0.8 parts, 1.2 to 1.5 parts of melamine polyphosphate.

4. The composite material according to any one of claims 1 to 3, characterized in that: The molecular weight of the PA6 resin is 60,000-800,000 Da; the molecular weight of the ultra-high molecular weight polyethylene is 5,000,000-6,000,000 Da.

5. The composite material according to any one of claims 1 to 3, characterized in that: The preparation method of the SiO2 aerogel-glass fiber is as follows: (1) soaking the glass fiber in an aqueous solution of 0.5-1wt.% HF+1.5-2wt.% NH4F for 20-30 seconds, washing with deionized water, and drying; preparing a solution of γ-aminopropyltriethoxysilane, anhydrous ethanol, and deionized water in a mass ratio of (0.03-0.05): 1:0.2, raising the temperature to 70-80°C, soaking the glass fiber and SiO2 aerogel in the above solution for 60-90 seconds, and using ultrasonic stirring during the soaking process; (3) filtering the solution of step (2), and heat-treating it at 100-120°C for 10-20 minutes to obtain SiO2 aerogel-glass fiber for later use.

6. The composite material according to claim 5, characterized in that The glass fiber has a length of 50 to 80 mm and an average fiber diameter of 5 to 10 μm.

7. A method for preparing a PA6 black non-absorbent composite material for automobile seats as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weigh the components in the appropriate proportions and set aside; (2) Pour PA6 resin, SiO2 aerogel, and carbon black into a stirring device and stir evenly to form material group A; (3) Pour ultra-high molecular weight polyethylene, SiO2 aerogel-glass fiber, MBS, ethylene-acrylate-maleic anhydride copolymer, antioxidant 1010, and melamine polyphosphate into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

8. The method for preparing a composite material according to claim 7, characterized in that: The set temperatures of the twin-screw extruder are: section one: 210-220°C, section two: 220-230°C, section three: 225-235°C, section four: 230-240°C, section five: 235-245°C, section six: 220-230°C, section seven: 215-225°C, section eight: 215-225°C, section nine: 220-230°C, and die head: 225-235°C.

9. The method for preparing a composite material according to claim 7, characterized in that: The rotation speed of the twin-screw extruder is 300-400 rpm.

Citation Information

Patent Citations

  • Antistatic pigment seat material and preparation method thereof

    CN107936540A

  • Low-smoke halogen-free flame-retardant nylon composite material and application thereof

    CN109749438A